Slow but sure: the potential of slow-release nitrogen fertilizers to increase crop productivity and farm profit in Nepal - Pandit, N.R.; Gaihre, Y.K.; Choudhary, D.; Subedi, R.; Thapa, S.B.; Maharjan, S.; Khadka, D.; Vista, S.P.; Rusinamhodzi, Leonard (Informa UK Limited, 2022)
Reduction of nitrogen (N) input in cropping systems is critical to reduce environmental pollution and achieve sustainable development goals. Multi-location field trials for maize (n = 120) and rice (n = 84) were conducted across nine districts in Nepal during 2018 and 2019 to assess the potential of polymer coated urea (PCU) and urea briquette (UB) to increase agronomic N use efficiency (AEN), crop productivity and farm profits over conventional urea (CU). Nitrogen rates applied in PCU and UB treatments were 22% to 50% lower than CU (120 and 100 kg N ha−1 for maize and rice respectively). In maize, both PCU (8.4 t ha−1) and UB (8.5 t ha−1) applied at 50% and 25% lower N rates respectively produced similar grain yields compared with CU (7.9 t ha−1). Similar results were observed in rice where PCU and UB applied at 22% less N led to a productivity of 5.4 and 5.5 t ha−1 respectively over CU (5.1 t ha−1). Moreover, both PCU and UB increased maize and rice yields significantly compared with current farmer’s practices (FP). In both maize and rice, PCU and UB significantly increased partial factor productivity of N (PFPN) and agronomic NUE (AEN) compared with CU. Furthermore, PCU and UB increased farmer’s net income by US$88 and US$148 in maize and by US$10 and US$87 in rice respectively. These results suggest that PCU and UB could save N input by 22-50% while maintaining similar or even higher yield and higher benefit to farmers compared with CU.